Cover of charity Christmas card - Farjeon, Eleanor, 1881-1965 ; Low, David, 1891-1963 (1938)
032-0001-001 CHRISTMAS IN SPAIN Bring to the dark Madonna no more myrrh, Bring to her Child No gold or frankincense. To him and her Lead no more asses piled With jars of spikenard and bales of silk. But to them bring Lavishly gifts of milk. Oh bring them milk Swiftly, shepherd and king! Lest the dark mother waking in the morn of Christmastide Sees on her bosom not the Christ new-born, But Christ the crucified. ELEANOR FARJEON LOW 292/946/32/1